HUBUNGAN TINGKAT STRES DENGAN KEJADIAN DISMENOREA PADA MAHASISWI KEPERAWATAN ANGKATAN VI SEKOLAH TINGGI ILMU KESEHATAN (STIKes) CITRA HUSADA MANDIRI KUPANG (CHMK) - Santi Liberty Mantolas (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2019)
Stres is adaptive respons, influenced by individual characteristic and psychoologis, consequence by action, situation, or external occurrence that cause psycal demand and anybody psycholoogis. While dismenorea is painful when menstruation. Painful menstruation disposed more aften happen and unusually on woman undergone stres. Purpose of this research to know the correlation stres level with dismenorea occurrence on nurse students generation VI at STIKes Citra Husada Mandiri Kupang. Design used in this research was correlational design with cross sectional approach. Population in this research was 96 respondences. Sampel this research was 77 respondences with used proposional stratified random sampling and simple random sampling. Result of this study test spearman rhobe obtained 0,005 < 0,05 it means that there was correlation stres level with dismenorea occurrence on nurse students generation VI at STIKes Citra HusadaMandiriKupang. Based on these results it can be concluded that there was correlation level of stres with dismenorea occurrence on nurse students generation VI at STIKes Citra Husada Mandiri Kupang. Keyword: level of stres, dismenore aoccrence, students.